Pathogenesis of Nonsteroidal Anti-Inflammatory Drug Gastropathy: Clues to Preventative Therapy - Salim MA Bastaki; John L Wallace (Canadian Journal of Gastroenterology)
Gastric ulceration and bleeding are major impediments to the chronic use of nonsteroidal anti-inflammatory drugs (NSAIDs). The development of effective therapies for prevention of these adverse effects requires better understanding of their pathogenesis. Several features of NSAIDs contribute to the development of damage in the stomach, including the topical irritant effects of these drugs on the epithelium, impairment of the barrier properties of the mucosa, suppression of gastric prostaglandin synthesis, reduction of gastric mucosal blood flow and interference with the repair of superficial injury. The presence of acid in the lumen of the stomach also contributes to the pathogenesis of NSAID-induced ulcers and bleeding in a number of ways. Acid impairs the restitution process, interferes with hemostasis and can inactivate several growth factors that are important in mucosal integrity and repair. Profound suppression of gastric acid secretion has been shown to be effective in preventing NSAID-induced ulceration. There is a strong possibility that new NSAIDs entering the market will have greatly reduced toxicity in the gastrointestinal tract.